A paratopia testemunho-documental e o discurso da negritude em Vencidos e Degenerados - Carreira, Rosângela Aparecida Ribeiro (2015)
The present study is inserted into French Discourse Analysis theoretical and methodological approach and aims to analyze and understand discourse strategies present in Vencidos e Degenerados , a novel by José Nascimento Moraes, which is an important part of the discourse of blackness that emanates from enunciation scenes. It also aims to evaluate the role of paratopia in the testimony and documental proxemics characterization. It is important subject, since the paratopia related to literary discourse as well as the discourse of blackness are issues still little explored academically, serving as general category for analysis in the literary context and of the black condition in Brazilian history. Our hypothesis is that the ideal of blackness presented in literary discourse embodied in testimony and documentary because it is constructed and legitimized from paratopies and atopies displacement intertwined with discursive historicity. We also assume that the testimony and documentary discourse presents this displacement movement to legitimize a discourse or an ideal that constitutes a kind of "stylistic or semiotic design" of testimonial speech, which we call discursive proxemics . In order to achieve our goals, we have mainly used as theoretical support the studies by Discourse Analysis from Maingueneau (2010, 2008a, 2008b, 2008c, 2007, 2006, 2001, 2000, 1996, 1992 and 1983), Charraudeau (2004, 2005 and 2012) and Foucault (1992, 2004, 2005a and 2005b). We have also used concepts of Literary Theory, Philosophy, Sociology and Anthropology extracted from Lucáks (2000), Bakhtin (2003), Benjamin (1985), De Marco (2004), Seligman -Silva (2006) and Bosi (1995), Fernandes (2006, 2008 and 2005-6), Munanga (2004, 2006, 2007 and 2009), Hall (2013), Fanon (2008), and Bhabha (1998). All of them have been taken as elements for understanding the discursive testimonial aspect and to support our vision of the socio-historical conditions of production. We have proved our hypothesis that the documentary evidence is given of paratopic shape and we have also extended the analysis of this category to other possibilities we call paratopies: authorship, aphasic, investigative, documentary, testimonial and testimonial-documentary